Leaving no one behind in Ghana through university education: Interrogating spatial, gender and class inequalities - Jasper Abembia Ayelazuno; Maxwell A. Aziabah (United Nations Research Institute for Social Development (UNRISD), 2021)
The number of higher education institutions in Ghana has soared in the last three decades and university enrolments have shot up in tandem. Yet the number of Ghanaians living in poverty is higher than ever before, and social inequality is on the rise. Against this backdrop, this paper critically examines the role universities play in addressing the problem of social inequality in Ghana. It specifically explores the possibilities and limitations Ghana faces in meeting the targets of the Sustainable Development Goals (SDGs), specifically SDG 4 on education. Based on analysis of secondary data, both qualitative and quantitative, the paper argues that the widening of participation in university education in Ghana is not inclusive in terms of gender, class or geographic location. Far from addressing inequalities in access to university education, the dynamics shaping the provision of university education in Ghana exclude marginalized social groups such as women and the poor, as well as the those living in rural areas and in the northern part of the country. The paper concludes by highlighting critical areas and issues needing further research to inform policy reforms aimed at widening access and promoting equity in higher education in Ghana.
Keywords: 330; Ghana; higher education; inequality; SDG 4; universities